Emotional Intelligence of Medical Post Graduate Students from Central India: A Cross Sectional Study - Ujwala U. Ukey; Sarita K. Sharma; Sanjeev M. Choudhary; Tushar S. Tathe (Journal of Preventive Medicine And Care, 2020)
Background Emotionally intelligent doctors are better able to perceive the need of the patient. In today’s world, where patient satisfaction is one of the most important criteria for a successful medical practice, emotional intelligence of doctors plays a vital role. Objectives To study emotional intelligence of post graduate medical students. Methods It is a cross-sectional study conducted in Government Medical College and Hospital, Nagpur during January- February 2019. The study participants were one hundred first - year post graduate students. Data collection was done using quick emotional intelligence self administered questionnaire. Data was entered in Microsoft office excels and analyzed with the help of epi info. Results In the present study total 100 post graduate students were assessed of which 56% were male. Emotional awareness and emotional management was better in male post graduate students in comparison with the females and the difference was found to be statistically significantly. The scores of the other two domains were almost equal in both. More than half of the study participants had a satisfactory EI score i.e. 25-34. Conclusion Male post graduate students had better EI. Most of the study participants had a satisfactory EI score.
Keywords: Emotional intelligence